The System of Infrastructure Ensuring Business Activity in the Market of Mobile Commerce of Russia - Alexey P. Isaev; Tatyana V. Vasilyeva (Управленческое консультирование, 2019)
Entrepreneurship in the mobile commerce market provides the opportunity to search for new opportunities for companies in the mobile environment. Taking into account the innovative nature of entrepreneurship in the mobile commerce market, it is necessary to form an infrastructure support system, the main tasks of which are: activating business processes in the mobile commerce system by creating the necessary conditions and turning business activities in this area into a real factor of economic growth by adapting the economy to advanced technologies. The article discusses the system of infrastructure support for entrepreneurship in the mobile commerce market as a complex of institutional entities that provide the conditions for implementing the processes of organizing and managing the development of entrepreneurial activities in the mobile commerce market in Russia. Thus, the infrastructure support of small business in the mobile commerce market is a combination of conditions, institutions and mechanisms that ensure the sustainable development and competitiveness of Internet companies in the Internet environment.